PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN FLIPBOOK DIKAITKAN DENGAN KEMAMPUAN KOMUNIKASIMATEMATIS SISWA SMA - Selvia, Selvia; Suratman, Dede; Hartoyo, Agung (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe method of this research uses Research and Development approach which consists of 4 stages, these are: initial data research and collection, plan and development, product developmant, and also evaluation and revision. The subjects of this research are students of X MIPA 1  SMAN l Bengkayang which are 30 students. The result shows that: (1) Based on validators’ appraisal, which are mathematics program’s lecturer of the Faculty KIP and also two mathematics teachers, learning media of mathematics in a form of flipbook is categorized as valid (2) Besed on the assessment from the observer about implementation, learning activities using instructional media in a flipbook’s form are categorized as practical. (3) Based on writtent test results of students’ mathematical communication skills it has gained 3.49 average score as good category while average score of students’ verbal communication skills is 3.85 as excellent category, so learning media in flipbook’s form is declared as effective.  Learning media, which uses flipbook and is associated with mathematical communication skills of students, meets quality criterias, these are: valid, practical and effectiveKeywords: Development Research, Flipbook, Mathematical Communication Skill, Probability, Quality.